THE SOCIAL COST OF FARMER-HERDER CONFLICTS IN ISEYIN,OYO STATE, NIGERIA (2023)
Farmer-herder conflict is one of the most prevalent violent occurrences in West Africa with attendant social cost, which include livelihood and socio-relational consequences. There have been frequent farmer-herder conflicts in Nigeria, which have resulted inmassive destruction of lives and property. Most studies on farmer-herder conflicts have focused mainly on causes, damages and casualties, with little attention paid to the social cost. This study, therefore, examined the effects of the conflicts on farmer andherder livelihoods, family structure and their symbiotic relationship, as well as the management structure employed to curtail farmer-herder conflicts in Iseyin, Oyo State. Group Conflict Theory was adopted as framework while the exploratory design was employed. Purposive sampling technique was used to select communities that experienced incessant farmer-herder conflicts at Iseyin. Snowball sampling technique was used to select the farmer and herder respondents. Two key informant interviews were conducted with leaders of farmers and herders. Sixty in-depth interviews were conducted with 30 farmers and 30 herders selected at Seraphim (6 farmers, 6 herders), Baale-sagbo (4 farmers, 5 herders), Awaye (6 farmers, 6 herders), Aba-paanu (5 farmers, 5 herders), Olugbade (4 farmers, 5 herders), Sangote (2 farmers, 2 herders) and Alagbe (3 farmers, 3 herders). Data were content-analysed. The prevalence of farmer-herder conflicts had adversely affected four principal elements of farmer and herder livelihood − security, income, health and education. Farmers and herders lived in constant fear of attack and destruction of lives and property. Also, farmers had witnessed significant decrease in farm produce because of the incessant destruction of farms; and herders lost herds due to retaliatory rustling and poisoning. There was a reduction in the income of farmers and herders owing to low output. Loss of income resulted in farmers’ failure to repay loans. Farmers accessed community healthcare, but herders had limited access to health facilities. The children of farmers and herders experienced disruption of their education as a result of their parents’ inability to pay the required fees. The families of both farmers and herders lost male breadwinners and family members, and made unplanned relocation to other communities. Prior to remarriage, farmers’ widows assumed the roles of family heads but the widows of herders were integrated into the extended family structure. Farmer-herder conflicts had made the symbiotic relationship of farmers and herders to degenerate into inter-community mistrust and discouragement of inter-communal marriages. It had also truncated intercommunity business relations. The conflict management strategies adopted by the herders and farmers included reporting incidence of conflict to group leaders and the police. That, in some instances, led to the compensation of aggrieved parties. The social cost of the conflicts between farmers and herders in Iseyin had a debilitating impact on their livelihoods and inter-group relations. Reports to group leaders and state authorities had brought about some compensation and peace to the communities. Farmers and herders should adopt conciliatory strategies to manage disagreements in peace and conflict periods.